Epistemic Verbs and the Expression of Knowledge in English and Mandarin - Alindra, Devi Alvionita; Manugeren, M; Barus, Efendi (Universitas Pahlawan Tuanku Tambusai, 2025)
Language and knowledge are fundamentally intertwined, shaping how individuals perceive, interpret, and express reality. This study investigates epistemic verbs as linguistic indicators of knowledge and belief within two distinct epistemological and cultural frameworks: English and Mandarin Chinese. By adopting a qualitative descriptive–comparative approach, grounded in functional linguistics and epistemic discourse analysis, this research explores how epistemic verbs reflect the ways speakers conceptualize truth, certainty, and cognition. The data were collected from authentic corpora—including dialogues, news articles, academic essays, and conversational transcripts—and analyzed through semantic, pragmatic, and cultural dimensions using triangulated methods. Findings reveal that English epistemic verbs (e.g., know, believe, think, guess) form a hierarchical and explicit epistemic system, emphasizing rational certainty, empirical evidence, and individual cognition, consistent with Western philosophical traditions. In contrast, Mandarin epistemic verbs (e.g., 知道 zhīdào, 认为 rènwéi, 觉得 juéde, 相信 xiāngxìn) display contextual, relational, and affective orientations, integrating emotion and social harmony in the expression of knowledge, reflecting an Eastern holistic worldview. Comparative analysis demonstrates that English expresses epistemic stance vertically, based on degrees of certainty, while Mandarin expresses it horizontally, emphasizing social context and relational appropriateness. These contrasts highlight deeper philosophical divides between Western rationalism and Eastern relational holism, suggesting that linguistic forms mirror epistemological ideologies. The study concludes that epistemic verbs are not mere grammatical categories but cognitive-cultural constructs that embody each society’s way of “knowing” and “believing.” Understanding these differences is vital for intercultural communication, as epistemic misalignment often leads to pragmatic misunderstanding between English and Mandarin speakers. This research contributes to the emerging field of cross-cultural epistemic linguistics, offering insights into how language, cognition, and culture collectively shape the human expression of knowledge.